Troublesome cough as the sole manifestation of pulmonary embolism - Aydanur Ekici; Şule İleri; Habibe Aslan; Mehmet Ekici (Respiratory Medicine Case Reports, 2019)
Early diagnosis and effective treatment to reduce mortality is the basis of pulmonary embolism. However, the diagnosis can be easily overlooked due to nonspecific clinical presentation. We present 9 cases of pulmonary embolism manifested by a symptom suggestive of an irritating cough due to viral upper respiratory tract infection (patients with no risk factors for PE). Pulmonary embolism should be considered in cases of irritating cough that does not respond to inhaler treatment, d-dimer positive and normal chest X-ray.